The Quality Of Marine Products And Fish Auction Places (TPI) As Determining Factors In The Welfare Of The Lubuk Pakam Fishing Community - Khairun Nisa; Ihsan Effendi; Ikbar Pratama; Adelina Lubis; Sugito Sugito (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of seafood product quality and the role of Fish Auction Places (TPI) on improving the welfare of fishing communities in Lubuk Pakam. As a coastal area with abundant fishery potential, local fishermen still face constraints such as limited storage, processing, and distribution facilities, which impact the quality of their catch. Furthermore, the role of TPI as a means of marketing seafood is not yet optimal, thus reducing its effectiveness in creating fair and transparent prices. This study used a quantitative method with an associative approach, involving 98 respondents, and analyzed through multiple linear regression. The results show that seafood product quality has a positive and significant effect on improving fishermen's welfare. Similarly, the role of TPI has been shown to have a positive influence on fishermen's income and bargaining position. Simultaneously, these two independent variables contribute significantly to improving the welfare of fishing communities. These findings confirm that the synergy between improving product quality and optimizing the function of TPI is an important key in encouraging the creation of sustainable fishermen's welfare.